Ethnobotanical survey of medicinal plants used by people cured of SARS-CoV-2 in the center of Algeria - Belmouhoub, Messaoud; Boubekeur, Aberkane; Tacherfiout, Mustapha; Boukhalfa, Farid; Khaled Khodja, Yazid; Bachir bey, Mostapha (Ethnobotany Research and Applications, 2024)
Background: The COVID-19 disease has affected more than 760 million people and caused more than 6,780,000 deaths worldwide. These numbers are likely to increase; however, the availability of the SARS-CoV-2 vaccine has slowed its rate of spread. On the other hand, several societies around the world have used many medicinal plants to prevent or treat this disease, particularly in regions with a long history of traditional medicine, like North African countries. Method: This study was conducted from February to November 2022 in three Algerian provinces (Bejaia, Bouira, and Tizi-Ouzou). The ethnobotanical information was obtained through a direct interview with 459 people cured of COVID-19. Results: In this investigation, 35 medicinal plants belonging to 21 families were registered, of which 74.29% are local and 25.71% are imported from other countries. The plants mostly used are Citrus limon L. (68.49%), Origanum vulgare L. (50%), Syzygium aromaticum L. (41.66%), Mentha spicata L. (35.68%), Zingiber officinale Roscoe (26.04%), Aloysia citrodora Palau. (21.09%), Allium sativum L. (8.59%), Citrus ×sinensis L. (8.33%), Eucalyptus globulus Labill. (8.07%), and Allium cepa L. (7.29%). Conclusion: This ethnobotanical survey, where information was collected from people cured of COVID-19, is the first in Algeria and probably in the world. Therefore, this study is an interesting contribution to the management of this epidemic, of which at present several cases are recorded throughout the world. Keywords: SARS-Cov-2, cured people, ethnobotanical survey, Algerian population, medicinal plant